Price Transmission Mechanism among Disaggregated Processing Stages of Food: Demand-Pull or Cost-Push? - Kwon, Daeheum (한국농촌경제연구원, 2013)
The recent concurrent surges of food and commodity prices renew the debate on the causal directions between producer and consumer prices. To address this issue, we utilize the stage of processing system incorporating retail stage beyond crude, intermediate, and finished processing stages of food and employ the method proposed by Toda and Yamamoto (1995) and Dolado and Lütkepohl (1996) of Granger causality tests. The overall results show that consistent with theory of derived demand, the demand-pull mechanism coexisted with the cost-push processes in 1985-2001. However, the upward cost-push pressures dominate the demand-pull mechanism through various transmission channels in 2002-2008.
Keywords: food price surge; price transmission mechanism; processing stages of food; Granger causality test; food price surge; price transmission mechanism; processing stages of food; Granger causality test